1997
DOI: 10.2337/diacare.20.9.1363
|View full text |Cite
|
Sign up to set email alerts
|

ACE Inhibitor Use Is Associated With Hospitalization for Severe Hypoglycemia in Patients With Diabetes

Abstract: The results show that the association between ACE inhibitor therapy and hospital admission for severe hypoglycemia is not explained by these confounding factors. Although ACE inhibitors have distinct advantages over other antihypertensive drugs in diabetes, the risk of hypoglycemia should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
2
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 12 publications
2
47
2
3
Order By: Relevance
“…In contrast with our findings, an association between treatment for severe hypoglycaemia and use of ACE inhibitors has been indicated in a few registry based studies [23,24]. These studies are, however, hampered by important clinical differences between cases and control group (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with our findings, an association between treatment for severe hypoglycaemia and use of ACE inhibitors has been indicated in a few registry based studies [23,24]. These studies are, however, hampered by important clinical differences between cases and control group (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Some evidence has been presented to suggest that predisposition to severe hypoglycaemia may also have some genetic basis. Herings et al [9] and Morris et al [10] have shown that the use of ACE inhibitors increased the risk of having a severe hypoglycaemic event in adults, but these studies were retrospective in design and the findings remain controversial [11][12][13][14]. The fact that a small proportion of patients experiences severe hypoglycaemia whereas other patients with similar glycaemic control remain spared indicates that genetic factors may contribute to an increased risk, and studies conducted in Denmark and Sweden have supported this notion [8,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that genetic factors may predispose to a susceptibility to severe hypoglycaemia. Studies have shown that the use of ACE inhibitors may be a factor in the incidence of hypoglycaemia in adults [9,10], but this still remains controversial [11][12][13][14], as these studies were retrospective in design and were unable to adjust for some important confounding variables.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1990s, sporadic reports raised the hypothesis that angiotensin converting enzyme inhibitors (ACEIs) might cause hypoglycaemia [1][2][3][4], seemingly confirmed by several studies [5,6]. Safety signals mentioning the risk of hypoglycaemia with ACEIs were promulgated.…”
Section: Introductionmentioning
confidence: 99%